Makanan bagi Pelajar dalam Persfektif Islam & Kesehatan (Tela’ah Kitab Ta’limul Muta’allim Karya Imam Az-Zarnuji) - Dita Durotun Nufus; Ahmad Fauzi; Moh Nur Arifin; Lalu Turjiman Amad (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2025)
Abstract: This research aims to find out the food that is good to be consumed by every knowledge seeker / santri / student in studying. So that they can achieve success, usefulness and blessings from the knowledge they get. This research uses qualitative methods with library research techniques, the book Ta'limul Muta'alim by Imam Az-Zarnuji as the main source used by researchers. The results of this study, there are several foods that can strengthen and weaken the memorisation of knowledge claimants / students / students. Eating kundar (frankincense) mixed with honey, and eating 21 Red Grapes every morning before eating anything, drinking honey, milk and eating dates and often shaving the toothbrush are foods and behaviours that can strengthen the memory of knowledge claimants. Whereas eating wet coriander, eating sour apples, seeing people being beaten, reading writings in graves, passing through rows of camels, throwing live dandruff on the ground and cantuk (wounding on the head to relieve dizziness) in the nape of the neck. sour food, fatty food, and haram or syubhat food are foods that can weaken memorisation. The knowledge claimants/students/students are expected to avoid market food because market food is easily exposed to unclean and dirty, and far from remembering Allah, S.wt. and closer to neglecting Allah, Swt.Keywords: Food, Students, Islam and health, Ta'limul Muta'allim.Abstrak: Penelitian ini bertujuan untuk mengetahui makanan yang baik dikonsumsi oleh setiap penuntut ilmu/ santri/ siswa dalam menuntut ilmu. Agar mereka dapat meraih kesuksesan, kemanfaatan dan keberkahan dari ilmu yang didapatnya. Penlitian ini menggunakan metode metode kualitatif dengan teknik library research, Kitab ta’limul muta’alim karangan Imam Az-Zarnuji sebagai sumber utama yang di gunakan oleh peneliti. Hasil penelitian ini, terdapat beberapa makanan yang dapat menguatkan dan melemahkan hafalan para penuntut ilmu/ santri/ siswa. Makan kundar (kemenyan) dicampur madu, dan makan 21 Anggur Merah setiap pagi sebelum makan apa-apa, minum madu, susu dan makan kurma dan sering bersiwak merupakan makan dan prilaku yag dapat menguatkan hafalan para penuntut ilmu. Sedangkan makan ketumbar basah, makan apel yang kecut, melihat orang yang dipacung, membaca tulisan di kuburan, melewati barisan unta, membuang ketombe hidup di tanah dan cantuk (melukai di bagian kepala untuk menghilangkan pusing) di bagian liang tengkuk. makanan asam, makanan berlemak, dan makanan haram atau syubhat merupakan makan yang dapat melemahkan hafalan. Para penuntut ilmu/ santri/ siswa diharapkan dapat menghidari maknan pasar hal itu dikarenakan makanan pasar mudah terkena najis dan kotor, dan jauh dari mengingat Allah, S.wt. dan lebih dekat melalaikan Allah, Swt Kata kunci: Makanan, Pelajar, Islam dan kesehatan,  Ta’limul Muta’allim.